Quantitative Analysis of Efficiency Improvement of a Propulsion Drive by Using SiC Devices: A Case of Study. (28th February 2017) - Kumar, Kundan; Bertoluzzo, Manuele; Buja, Giuseppe; Ortenzi, Fernando
Abstract : One of the emerging research topics in the propulsion drive of the electric vehicles is the improvement in the efficiency of its component parts, namely, the propulsion motor and the associated inverter. This paper is focused on the efficiency of the inverter and analyzes the improvement that follows from the replacement of the silicon (Si) IGBT devices with silicon carbide (SiC) MOSFETs. To this end, the paper starts by deriving the voltage-current solicitations of the inverter over the working torque-speed plane of the propulsion motor. Then, a proper model of the power losses in the inverter over a supply period of the motor is formulated for the two types of device, including the integrated freewheeling diode. By putting together the voltage-current solicitations and the device power losses, the efficiency maps of the Si IGBT and SiC MOSFET inverters are calculated and compared over the torque-speed plane. The results for the Si IGBT inverter are supported by measurements executed on a marketed C-segment compact electric car, while the SiC MOSFET loss model is validated by an on-purpose built test bench. Finally, the overall efficiency of the propulsion drive is calculated by accounting for the motor efficiency. Main outcomes of the paper is a quantitative evaluation of both the improvement in the efficiency achievable with the SiC MOSFETs and the ensuing increase in the electric car range.